RESULTS AND PROSPECTS FOR THE DEVELOPMENT OF THE BELARUSIAN-CHINESE COOPERATION THE SILK ROAD ECONOMIC BELT - Khodoskina, O. A.; Igraieva, A. A.; Naumova, V. Y. (Science and Transport Progress, 2021)
Purpose. The most ambitious economic and geopolitical project at present is the New Silk Road initiative, which can radically modify transport and cash flows in Eurasia and around the world. It includes the Silk Road Economic Belt and 21st Century Maritime Silk Road projects and involves the creation of an extensive infrastructure network on the way from the western borders of China through the countries of Central Asia and Iran to Europe. Therefore, the purpose of this work is a detailed comprehensive study and analysis of the development of the Belarusian-Chinese cooperation on the Silk Road Economic Belt project, as well as determination of its further prospects. Methodology In the course of the study, we used statistical, territorial-sectoral and retrospective analysis with elements of economic and mathematical modeling of the functioning of economic systems. Findings. The Republic of Belarus has become the most important link in the creation of the Silk Road Economic Belt. It has a unique geographical advantage, extremely convenient economic and cultural conditions, being a key country in Eastern Europe, located at the junction of the European Union, and the Eurasian Economic Union. The country attracts with a developed transport infrastructure, a high level of education and professional resources. The New Silk Road project is focused primarily on railway communication. The main potential for the Republic of Belarus in transit traffic is associated with the use of containers. It is containerized cargo transportation that is actually the only way to transport goods in Eurasian transit. Originality. At this stage of project development, the construction of a full-scale functional, effective model that would allow predicting the results of the implementation of a specific subproject with the required accuracy is currently impossible. However, at the present stage, the originality is the so-called «problem statement» based on the obtained analytical data. They allow identifying existing problems during project implementation, formulating possible solutions and using them during economic analysis of the efficiency of other international projects of the analytical type (solving analytical economic problems). Practical value. The article discusses the prospects and difficulties of the development of transportations by express container trains of goods and cargo from the People’s Republic of China (PRC) to the Republic of Belarus. To overcome the imbalance in foreign trade with China, measures were proposed to solve this problem; attention was paid to the project for the construction of Eurasia high-speed highway (HSR), which should connect China with Western Europe through Russia and Belarus.